2016
DOI: 10.1111/rda.12856
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic possibilities from a serum sample—Clinical value of new methods within small animal reproduction, with focus on anti‐Müllerian hormone

Abstract: ContentsDuring the last decade, analysis of anti-Müllerian hormone (AMH), highly conserved between mammalian species, has contributed to new information in reproductive endocrinology, due to clinically available diagnostic assays. AMH is produced solely in the gonads, in the Sertoli cells of testes and granulosa cells of the ovary, and thus offers possibilities to diagnose physiologic and pathologic conditions involving these organs. This article reviews indications for AMH analysis in cats and dogs, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 65 publications
0
6
0
3
Order By: Relevance
“…Although most research on immunoassay interference involves human medicine studies, a few recent studies have shown that interfering antibodies in canine serum affected BNP (B-type natriuretic peptide), and possibly AMH (anti-M€ ullerian hormone) assay results. 8,9 Despite the potentially harmful impact on patient care, knowledge about antibody interference within veterinary medicine remains very limited. If the situation is comparable to that in human medicine, antibody interference might be a problem in veterinary medicine as well.…”
mentioning
confidence: 99%
“…Although most research on immunoassay interference involves human medicine studies, a few recent studies have shown that interfering antibodies in canine serum affected BNP (B-type natriuretic peptide), and possibly AMH (anti-M€ ullerian hormone) assay results. 8,9 Despite the potentially harmful impact on patient care, knowledge about antibody interference within veterinary medicine remains very limited. If the situation is comparable to that in human medicine, antibody interference might be a problem in veterinary medicine as well.…”
mentioning
confidence: 99%
“…Interference in this assay could lead to unnecessary surgery if patients are incorrectly determined to be unneutered. There have been reports of potentially erroneous AMH results in this assay since it was first evaluated in canine samples, and antibody interference has previously been described in people …”
Section: Introductionmentioning
confidence: 99%
“…A hiperplasia e hipertrofia das células prostáticas são mediadas pelo aumento da síntese hormonal de di-hidrotestosterona que, por sua vez, modula a expressão do agente mitogênico VEGF (fator de crescimento vascular e endotelial) (CARSON;RITTMASTER, 2003;STACHON et al, 2009), e, consequentemente, promove a angiogênese local (STACHON et al, 2009 (JUNIEWICZ et al, 1993;LAROQUE et al, 1994 POULSEN NAUTRUP, 2001;POLISCA et al, 2013;ZELLI et al, 2013). (FRENETTE et al, 1985;KRAKOWSKI et al, 2015;HOLST et al, 2017 Neste experimento, embora as concentrações séricas de estrógeno e testosterona encontravam-se dentro do limite de normalidade para cães (BRENDLER et al, 1983), os níveis hormonais dos cães hígidos foi superior aos doentes. A reduzida concentração de testosterona e, consequentemente, a redução na conversão estrogênica (ABNEY, 1999), são consideradas patogênicas para o desenvolvimento da HPB, uma vez que estimula a formação de novos receptores androgênicos na próstata (KRAWIEC, 1994;LEE, 1996).…”
Section: Discussionunclassified
“…O papel desempenhado pelo plasma seminal é fornecer o suporte e transporte para os espermatozoides durante a ejaculação (SMITH, 2008). A composição do fluido prostático em cães é basicamente de citrato, lactato, colesterol, sais, glicoproteínas, tais como a CPSE (proteína específica prostática canina) e antioxidantes enzimáticos, como a superóxido dismutase e glutationa peroxidase (FRENETTE et al, 1985;ANGRIMANI et al, 2014;KRAKOWSKI et al, 2015;HOLST et al, 2017) Ademais, a próstata desempenha função primordial na dinâmica da testosterona (IEHLÉ et al, 1995), pois é responsável pela metabolização da testosterona livre em di-hidrotestosterona (DHT), pela ação da enzima 5α-redutase (SHIDAIFAT; LIN, 2012). Dentre as funções da DHT, está a formação dos órgãos genitais externos masculinos durante a fase do desenvolvimento embrionário (AMORY et al, 2008).…”
Section: Funções Da Próstataunclassified
See 1 more Smart Citation